THE EFFECT OF SERVICE QUALITY ON CUSTOMER SATISFACTION, CUSTOMER DELIGHT AND CONSUMER LOYALTY AT LEGENDARY RESTAURANTS IN MALANG CITY - Riyadi, Sahrul Dwi; Wahyuningtyas, Agustina Shinta Hartati; Andriani, Dwi Retno (Socio-Economics/Agribusiness Department, 2023)
The competition in the restaurant industry is very tight, with many competitors that have sprung up with various strategies, such as providing the best quality of service to their consumers. This is also experienced by legendary restaurants A, B, C, and D, which have been selling culinary specialties of Malang City for decades with recipes that have been passed down from generation to generation. The experience of non-optimal service quality will affect customer satisfaction and can affect the level of consumer loyalty to legendary restaurants. Therefore, it is very important to conduct this research to determine the effect of service quality on customer satisfaction and loyalty, as well as the role of brand image in moderating it. This research was analyzed using SEM-PLS with 100 respondents. This research shows that the service quality provided by the four restaurants has a positive and significant impact on customer satisfaction, customer delight, and customer loyalty because the quality of service provided by the four restaurants is considered good.